Integrating ethical and Islamic spirituality values in improving Malaysian Umrah service quality - Suib, Fatin Husna (2018)
This study explores a body of work under the concepts of ethics and Islamic spirituality that associate with Malaysian Umrah service quality. Due to the rising unethicality cases within this service, it is crucial to propose a solution and deepen the comprehension towards ethicality supported by Islamic spirituality concept. The literature appears to be broadly divided into ethics and Islamic spirituality concept from the service industry. These concepts were connected and several values are derived from them. Subsequently, the values are being utilized through several organizational tools (example, code of conduct) and they further associate with three theories including deontology, virtue ethics, and spiritual leadership theory. Furthermore, a framework called Value Management System (VMS) was introduced as a solution to improve Malaysian Umrah service quality. The framework contains values from ethics and Islamic spirituality concepts, selected theories, and organizational tools. Moreover, this study takes the form of qualitative case study through in-depth interviews among Malaysian Umrah organizations and their customers. The research framework presented in this study function as a guideline to evaluate its findings. Moreover, through five research questions and framework in this study, its findings were revealed in three areas, identified as basic values (BV), VMS model and service quality feedbacks. BV is the combination of ethical and Islamic spirituality values with values’ from findings in this study. The researcher concluded there are 7 overlap BV listed as 1) justice/fair; 2) hard work; 3) honesty; 4) loyalty; 5) respect; 6) responsible and 7) sincerity. These values were included in the first step of the VMS model along with other elements such as vision and mission statements. Subsequently, the researcher managed to discover other VMS’ elements in its second and third step. These elements are a code of conduct, whistleblowing, training, and corporate disclosure policy; compliance, corporate social responsibility (CSR) and ethics audit program. Eventually, the existences of these VMS’ elements were giving a positive influence towards Malaysian Umrah customers’ feedbacks and service quality, with 50 positive responses compared to 14 on the negative side. The results suggest that consideration must be made with regards to the application of VMS’ model by Malaysian travel agencies. Any BV need to be selected by these organizations to be utilized into all of their organizational system suggested in the VMS model. Furthermore, Ministry of Tourism and Culture Malaysia (MOTAC) may take a significant role to monitor VMS’ application effectiveness among Malaysian travel agencies through their business licensing and code of ethics and conduct (COE&C) as a firm guideline for these agencies to follow. On the other hand, this study proposes that future Malaysian Umrah customers should be more aware of the legality of these agencies before purchasing any Umrah services. However, if these customers get cheated or their promises were not fully fulfill by these agencies during their Umrah journey, they should make a full complaint to MOTAC in order to claim any loss incurred.